2014
DOI: 10.3390/rs61110571
|View full text |Cite
|
Sign up to set email alerts
|

Ground Surface Response to Geothermal Drilling and the Following Counteractions in Staufen im Breisgau (Germany) Investigated by TerraSAR-X Time Series Analysis and Geophysical Modeling

Abstract: Abstract:The city of Staufen im Breisgau in southwest Germany suffers from a localized land uplift, which has occurred in the past six years in relation to geothermal drilling activities in 2007. So far, severe damages at 269 buildings have been recorded. The chemical transformation of anhydrite and water to gypsum, resulting in a volume increase, has been attributed as the cause of the uplift. Previous studies provide knowledge on the spatio-temporal displacement evolution from 2008 through 2011 using levelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…random variations of volume percentages of anhydrite and gypsum) and the not currently available deep data. In this respect, as a final remark, it is worth noting that the anhydrite/gypsum transformation has been observed to cause consistent and sudden uplift phenomena on other sites, such as the city of Staufen, Germany (Lubitz et al 2014), causing serious infrastructure damages.…”
Section: A Geological Interpretationmentioning
confidence: 99%
“…random variations of volume percentages of anhydrite and gypsum) and the not currently available deep data. In this respect, as a final remark, it is worth noting that the anhydrite/gypsum transformation has been observed to cause consistent and sudden uplift phenomena on other sites, such as the city of Staufen, Germany (Lubitz et al 2014), causing serious infrastructure damages.…”
Section: A Geological Interpretationmentioning
confidence: 99%
“…Additionally, the recent discoveries of oil deposit and drilling leads to ground deformation. Related studies have demonstrated the relationship between ground subsidence and oil drilling (Lubitz, Motagh, & Kaufmann, 2014;Zhang, Lu, & Kim, 2018). It is on this basis that the area was selected for deformation analysis using ALOS PALSAR data.…”
Section: Study Areamentioning
confidence: 99%
“…This includes active mining but also the effects of already sealed underground mines on above-ground settlements. Furthermore, the impact of geothermal drilling is investigated [56].…”
Section: Anthropospherementioning
confidence: 99%